Does Leadership Style Matter for Enhancing Economic Performance? - Budhathoki, Krishnahari (Economic Journal of Nepal, 2019)
This paper is an analysis of determinants of political leadership on economic performance. It reviews the theoretical and empirical literature on theroles of political leadership in economic growth. It adds to the literature on understanding of the impact of political leadership styles on economic advancement of a country, and suggests future directions for research in this area. Though qualitative method of inquiring on review of literature, the paper analyses the role of national political leadership style in the oretical basis of Goleman six leadership styles on the economic performance of a country like coaching, authoritative, afflictive,  democratize, pacesetting and coercive styles of leadership. This study primarily focuses on the leadership styles of the founding leader of Singapore, Lee Kuan Yew (LKY) and his economic performance on Singapore's economy. Considering the history of great personalities in the world as true leaders, who have constructively changed the history of their nations, leadership style plays important role in formulating and implementing of economic policies and actions. The study shows that LKY embraces all leadership styles indifferent scope and heights to get positive economic performance and to avoid constraints of economic environment.